Effects of tannic acid in streptozotocin-induced sporadic Alzheimer's Disease: insights into memory, redox status, Na+, K+-ATPase and acetylcholinesterase activity. (2nd January 2022) - Gerzson, Mariana F. B.; Pacheco, Simone M.; Soares, Mayara S. P.; Bona, Natália P.; Oliveira, Pathise S.; Azambuja, Juliana H.; da Costa, Pauline; Gutierres, Jessié M.; Carvalho, Fabiano B.; Morsch, Vera M.; Spanevello, Roselia M.; Stefanello, Francieli M.
Abstract: The aim of this study was to investigate the ability of tannic acid (TA) in preventing memory deficits and neurochemical alterations observed in a model for Sporadic Dementia of Alzheimer's Type. Rats were treated with TA (30 mg/kg) daily for 21 days, and subsequently received intracerebroventricular injection of streptozotocin (STZ). We observed that STZ induced learning and memory impairments; however, treatment with TA was able to prevent these effects. In cerebral cortex and hippocampus, STZ induced an increase in acetylcholinesterase activity, reduced Na +, K + -ATPase activity and induced oxidative stress increasing thiobarbituric acid-reactive substances, nitrites and reactive oxygen species levels and reducing the activity of antioxidant enzymes. Treatment with TA was able in prevent the major of these neurochemical alterations. In conclusion, TA prevented memory deficits, alterations in brain enzyme activities, and oxidative damage induced by STZ. Thus, TA can be an interesting strategy in the prevention of Sporadic Alzheimer's Disease.